2019
DOI: 10.14744/tjtes.2019.30232
|View full text |Cite
|
Sign up to set email alerts
|

Fournier’s Gangrene: Review of 36 Cases

Abstract: BACKGROUND: Fournier's gangrene (FG) is a very rare disease in daily urological practice. Despite medical improvements, mortality in FG is still high. Early diagnosis is very important to reduce additional instrumentations and mortality. In this study, we aimed to present the characteristics of the patients with Fournier's gangrene followed in two centers during ten years period. METHODS: The medical records of patients with FG were reviewed retrospectively. The patient characteristics, causative pathogens, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…Although only 18% required transfusion in a study by Benjelloun, more than half of our patients required blood transfusion [11]. Renal impairment occurred in about onethird of patients compared to what was reported in a recent study by Caliskan et al [12] The organism most commonly identified in this study was E. coli, similar to the findings of other studies [8,13].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although only 18% required transfusion in a study by Benjelloun, more than half of our patients required blood transfusion [11]. Renal impairment occurred in about onethird of patients compared to what was reported in a recent study by Caliskan et al [12] The organism most commonly identified in this study was E. coli, similar to the findings of other studies [8,13].…”
Section: Discussionsupporting
confidence: 88%
“…None of our patients had their testis removed in contrast to the findings of some recent studies [12,15]. This is because the testes derive their blood supply from the gonadal artery a branch of the aorta whereas the scrotal and penile skin obtain their arterial supply from the internal and external pudendal arteries [1].…”
Section: Discussionmentioning
confidence: 67%
“…In most of the previously published studies, the presence of DM in patients with FG has been shown as one of the major prognostic factors for morbidity and mortality [1,16,[20][21][22]. Nevertheless, some researchers did not report significant associations between DM and FG [2,3,19].…”
Section: Discussionmentioning
confidence: 99%
“…Then bacterial spread causes obliterative endarteritis, resulting in aggressive ischaemic necrosis of the fascia, and the affected areas turn into ulceration skin gangrene with sensory loss after 3-8 days, or even bacteraemia and septic shock in severe cases [4]. The most common pathogen of FG is polymicrobial organisms involving mixed aerobes and anaerobes, followed by Escherichia coli and Streptococcus [5,6]. Here, we report a rare case of FG mixed with A. turicensis infection.…”
Section: Introductionmentioning
confidence: 91%